(untitled) (Research, Society and Development, 2020)
The high consumption of plastic products generates several impacts, mainly associated with its waste. Due to its characteristics, the possibilities of disposal of this waste are reduced, so that its use as by-products comprises the best solution for the management of this waste. In this context, research has emerged that uses the residue of plastic products, such as post-consumer polyethylene tereftalate (PET), as a substitute for the natural aggregate in cement products. The production of these materials intends to work in parallel two socio-environmental objectives: the reduction of consumption of natural aggregates and the reuse of plastic waste in construction materials. This work will present data related to research on the production of cementitious mortars with partial replacement of natural sand by light aggregate of PET waste (ALRP) aiming at the realization of the state of the art contributing to the methodological basis of future research on the subject. For that, systematic searches were carried out in the ScienceDirect, Web of Science and Scopus databases, using descriptors, logical operators and temporal constraint application. In addition to presenting the main research data, an approach will be made on the importance of the problems associated with the theme and the parameters to be met by this new ecological material based on the concepts of sustainable construction.